2008
DOI: 10.1177/0093854808314786
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy, Intelligence, and Recidivism in Child Molesters

Abstract: The authors studied the relationships between psychopathy, intelligence, and offending in a sample of treated child molesters ( N = 216). Regression analyses showed that psychopathy (as measured by the Psychopathy Checklist—Revised) was strongly related to both offense history and recidivism during follow-up. Intelligence (assessed using four-subtest short forms of the Wechsler Adult Intelligence Scale—Revised and Third Versions) was not related to offending. However, there was a significant interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 28 publications
2
32
1
1
Order By: Relevance
“…This effect is somewhat larger than the effect reported by Hanson and MortonBourgon (d = 0.29), falling beyond the upper end of their 95% confidence interval (CI) [.20, .38]. There was, however, considerable variability in predictive effects (see Table 3), with effects from individual studies ranging from á = -0.18 (Sjöst-edt & Langström, 2002) to d = 0.96 (Beggs & Grace, 2008). None of these effects was clearly an outlier, however, with all effects falling within two standard deviations from the mean Note.…”
Section: Sexual Recidivismmentioning
confidence: 74%
See 1 more Smart Citation
“…This effect is somewhat larger than the effect reported by Hanson and MortonBourgon (d = 0.29), falling beyond the upper end of their 95% confidence interval (CI) [.20, .38]. There was, however, considerable variability in predictive effects (see Table 3), with effects from individual studies ranging from á = -0.18 (Sjöst-edt & Langström, 2002) to d = 0.96 (Beggs & Grace, 2008). None of these effects was clearly an outlier, however, with all effects falling within two standard deviations from the mean Note.…”
Section: Sexual Recidivismmentioning
confidence: 74%
“…In both of the latter scenarios, clinicians may still have ample access to law enforcement records but may have less opportunity to observe and interact with offenders over extended time. Whatever the reason, the Beggs and Grace (2008) study was clearly an outlier; other field studies found much weaker predictive effects for the PCL-R.…”
Section: Fieid Versus Research Scoresmentioning
confidence: 87%
“…Raymond, Coleman, Ohlerking, Christenson, and Miner (1999) found that 22.5% of sex offenders with paedophilia suffer from antisocial personality disorders. Beggs and Grace (2008) found that 4.6% of sex offenders that committed crimes against children suffered from psychopathy (measured by the PCL-R), which is remarkably lower than the prevalence of psychopathy among offenders in general (around 20%). Although a considerable percentage of sex offenders suffer from antisocial/psychopathic personality disorders, it is important to consider the differences between sex offenders suffering from paedophilia International Journal of Law and Psychiatry xxx (2015) xxx-xxx without (severe) antisocial/psychopathic co-morbidity and those suffering from paedophilia with (severe) antisocial/psychopathic comorbidity.…”
Section: Introductionmentioning
confidence: 87%
“…Overall, additional contemporary researchers have found the relationship between intelligence measures and PCL scores to be generally weak, leaving us with little evidence to believe that individuals with psychopathic tendencies possess superior intelligence [26,27]. Yet, contrary to the previously mentioned researchers, others have found significant relationships between some aspects of intelligence, such as verbal abilities, and emotional intelligence [28,29], and total PCL scores. Johansson and Kerr [30] for instance found that higher IQ, particularly verbal intelligence, meant an earlier start in violent crime.…”
Section: Materials and Methodologymentioning
confidence: 76%